1993
DOI: 10.1128/aem.59.4.987-996.1993
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of broiler chickens by waterborne Campylobacter jejuni

Abstract: was supplied with fresh chicken by a single wholesaler (wholesaler A), who obtained all of the chicken that it distributed from a single farm. This farm and its immediate surroundings were investigated to determine the source(s) of the organisms colonizing the chickens. Evidence was obtained that poultry from the farm caused sporadic human campylobacteriosis in the population served by the farm for at least 18 months after the recognition of the catering college outbreak. A report on this investigation is bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(114 citation statements)
references
References 35 publications
3
107
1
Order By: Relevance
“…Rollins and Colwell (1986) did provide some preliminary evidence suggesting that the reversion from coccoid to spiral forms occurred following animal passage. Nonculturable forms of Campylobacter spp., observed in water supplies by direct immunofluorescence microscopy, were able to give rise to colonization of chickens following consumption of this water (Pearson et al 1993), supporting the existence of a resuscitative VBNC form. Further investigations showing the resuscitation of putative VBNC cells in laboratory animals (Jones et al 1991;Saha et al 1991;Stern et al 1994;Tholozan et al 1999), aquatic environments (Thomas et al 2002) and after acid treatment (Chaveerach et al 2003) have been reported.…”
Section: Viable But Nonculturable Statementioning
confidence: 66%
“…Rollins and Colwell (1986) did provide some preliminary evidence suggesting that the reversion from coccoid to spiral forms occurred following animal passage. Nonculturable forms of Campylobacter spp., observed in water supplies by direct immunofluorescence microscopy, were able to give rise to colonization of chickens following consumption of this water (Pearson et al 1993), supporting the existence of a resuscitative VBNC form. Further investigations showing the resuscitation of putative VBNC cells in laboratory animals (Jones et al 1991;Saha et al 1991;Stern et al 1994;Tholozan et al 1999), aquatic environments (Thomas et al 2002) and after acid treatment (Chaveerach et al 2003) have been reported.…”
Section: Viable But Nonculturable Statementioning
confidence: 66%
“…Studies in many countries have shown that drinking water can be a direct source of human infection (Abe et al, 2008;Uhlmann et al, 2009;Karagiannis et al, 2010;Gubbels et al, 2012). Perhaps, more importantly, the environment is also an important source for the primary and secondary colonisation of food animals, particularly chickens (Pearson et al, 1993;Ogden et al, 2007;Perez-Boto et al, 2010). It is likely that routes of transmission flowing through the environment, farm animals and wild animals through to humans interact in complex ways (Fig.…”
Section: The Natural and Farmland Environment As A Reservoir Or Sourcmentioning
confidence: 99%
“…It has been reported that C. jejuni can respond to unfavourable conditions, including low nutrient environments, by entering a VBNC state (Rollins & Colwell, 1986;Pearson et al, 1993;Murphy et al, 2006) and that oxygen can accelerate this transition to VBNC (Klancnik et al, 2006). In the VBNC state, bacteria lose the ability to form colonies on normal growth media and reduce their metabolic activity but retain viability and the potential to recover, and even cause infections (Barer & Harwood, 1999).…”
Section: The Viable But Nonculturable (Vbnc) Statementioning
confidence: 99%
“…Waterborne outbreaks of Campylobacter occur occasionally and are normally associated with faecal contamination of the water source from agricultural waste run-off, bird droppings or sewage outflow (Bobb et al 2003;Clark et al 2003;Hanninen et al 2003). Contaminated groundwater may serve as a source of inoculation of drinking waters with C. jejuni or the introduction of the organism into livestock populations where groundwater is used as a source of drinking and irrigation (Pearson et al 1993;Stanley et al 1998;Hanninen et al 2003). The survival of C. jejuni in groundwater is not surprising as the environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%